Salespeople s Personal Values The Case of Western Pennsylvania - Harcar, Tijen; PAKSOY, MAHMUT (My University, 2006)
Shared personal values of the members in an organization are crucial for the longterm success and employee satisfaction. A key contribution of this study is measurement of the personal values of the salespeople in Western Pennsylvania. Schwartz’s Value Inventory has been used for the measurement.
Keywords: Performans--Yönetim; Performans Ölçümü; Performance--Management; Performance Measurement